2007
DOI: 10.1155/2007/60964
|View full text |Cite
|
Sign up to set email alerts
|

Expression Divergence of Tandemly Arrayed Genes in Human and Mouse

Abstract: Tandemly arrayed genes (TAGs) account for about one third of the duplicated genes in eukaryotic genomes, yet there has not been any systematic study of their gene expression patterns. Taking advantage of recently published large-scale microarray data sets, we studied the expression divergence of 361 two-member TAGs in human and 212 two-member TAGs in mouse and examined the effect of sequence divergence, gene orientation, and chromosomal proximity on the divergence of TAG expression patterns. Our results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
0
7
1
Order By: Relevance
“…Although reduced sample sizes resulted in reduced statistical significance, the pattern of the greatest impact #CTCF on expression divergences held regardless of the orientation of paralogs (Table 3). Using microarray expression data, a previous study found that intergenic distance was related to expression divergence for tandemly arrayed paralogs [30]. However, microarray data is known to have cross-hybridization related biases [17], and we found no direct association between intergenic distance and expression divergence for tandemly arrayed paralogs after controlling for #CTCF and Δ CpG O/E (see ρ p of d vs. ExpD 1-r or ExpD Euc , Table 2).…”
Section: Resultscontrasting
confidence: 52%
“…Although reduced sample sizes resulted in reduced statistical significance, the pattern of the greatest impact #CTCF on expression divergences held regardless of the orientation of paralogs (Table 3). Using microarray expression data, a previous study found that intergenic distance was related to expression divergence for tandemly arrayed paralogs [30]. However, microarray data is known to have cross-hybridization related biases [17], and we found no direct association between intergenic distance and expression divergence for tandemly arrayed paralogs after controlling for #CTCF and Δ CpG O/E (see ρ p of d vs. ExpD 1-r or ExpD Euc , Table 2).…”
Section: Resultscontrasting
confidence: 52%
“…This dataset was generated by hybridization of RNAs from unpollinated stigma at anthesis, seedling shoot, seedling root, mature anther, ovary at anthesis, seeds of five days after pollination, 10-day-old embryo, 10-day-old endosperm as well as suspension cell on 57K Affymetrix rice whole genome array. To evaluate the tissue specificity for ALDH genes, we calculated the tissue specificity index, τ as described (Shoja et al, 2007). For three genes (OsALDH2-3, OsALDH2-4 and OsALDH3-2) with more than one unique probe, we selected the probe with higher intensity value for calculation.…”
Section: Evaluation Of Rice Aldh Gene Expression Patterns Using Micromentioning
confidence: 99%
“…OsALDH3-5 was excluded because of its extremely low expression signal. The τ value ranges from 0 to 1, with higher value indicating higher tissue specificity (Shoja et al, 2007). Most genes in multiple-member families exhibited high τ values, indicating high tissue specificities for their expression patterns (Fig.…”
Section: Expression Of Duplicated Aldh Genes Showed High and Distinctmentioning
confidence: 99%
“…Each chip was filtered to remove the probes which represent more than one gene. If a gene is represented more than once, we removed at first the lower confidence probe(s) of this gene (Affymetrix probes with name "_x_at" or "_s_at", Huminiecki andWolfe, 2004 andShoja et al, 2007) and then randomly selected one to represent it if it still had more than one probe after removing the lower confidence probe(s). The data were normalized for further calculating Pearson correlation coefficient, using robust multi-array average (RMA) method (Bolstad et al, 2003).…”
Section: Microarray Datamentioning
confidence: 99%